Parental Support in Building Children's Motivation for Pushbike Sports - Danang Sukma Prayoga; Fery Darmanto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to analyze the role of parental support in fostering children’s motivation to participate in pushbike activities in Pekalongan City. The study employs a qualitative descriptive approach supported by quantitative descriptive data. Data collection was conducted through questionnaires, interviews, observations, and documentation, involving parents and children participating in pushbike activities. Quantitative data analysis was performed using descriptive statistics with the aid of SPSS, while qualitative data analysis utilized NVivo through visualizations such as word clouds, mind maps, project maps, and hierarchy charts. The results indicate that parental support plays a significant role in enhancing children’s motivation to participate in pushbike sports. Emotional support, manifested through attention, encouragement, and guidance, helps boost children’s self-confidence and comfort during training and competitions. Instrumental support through the provision of facilities and training needs also contributes to children’s enthusiasm for sports. Additionally, direct parental involvement, positive instructional approaches, peer interactions, and conflict resolution help create an environment that supports children’s physical, social, and psychological development. Thus, parental support is a key factor in build-ing children’s motivation to participate in pushbike sports in Pekalongan City.